Environmental and economic assessment of the application of an optimised chemical decontamination method on the internal surface of a nuclear steam generator - Rachael Clayton; Anthony Banford; Laurence Stamford (Results in Engineering)
Deep geological disposal facilities for radioactive waste are built with finite capacity and high cost. Therefore, waste volume minimisation via pre-treatment is paramount. This paper presents the first life cycle environmental and economic sustainability assessment of a chemical metallic decontamination method, including investigation during laboratory-scale development and evaluation of a nuclear steam generator case study. Initial life cycle assessment (LCA) discovered environmental hotspots in oxalic acid, hydrogen peroxide, and heating requirements, which were significantly reduced by the process developers during optimisation. Incorporating LCA and LCC in the development phase contributed to a reduction in climate change impacts of 45 % (from 971 t CO2 eq. to 532 t CO2 eq. per steam generator) and costs of 13 % (€2.72 M to €2.36 M). Sensitivity analysis revealed an 11 % cost reduction when the treated steam generator is classified as very low-level waste. Other disposal routes increased costs (from +95 % to +798 %) and environmental impacts (e.g., +186 % to +542 % for climate change) due to the absence of steel recovery through recycling. Two key implications are that chemical decontamination and recycling of radioactive metallic structures offer substantial environmental and economic improvements, and that integration of LCA and LCC in waste processing R&D can enable major savings.